Study on practice of physical activity among medical interns in a private medical college hospital in Chennai - Boopathirajan, Ramkumar; Raveendran, Aswathy; Ayyalusamy, Pavithra (International Journal Of Community Medicine And Public Health, 2019)
Background: Physical inactivity is one of the leading risk factors for death worldwide. It is a key risk factor for non-communicable diseases (NCDs) such as cardiovascular diseases, cancer and diabetes. Physical activity has significant health benefits and contributes to prevent NCDs. Globally, 1 in 4 adults are not active enough. More than 80% of the world’s adolescent population is insufficiently physically active. So the aim of this study is to assess the practice of physical activity among the medical interns, as they are the future doctors. Methods: A cross sectional study was conducted among 124 medical interns. A pre-tested, semi-structured questionnaire was used to collect the data. Microsoft Excel 2010 spread sheet version 14.1.3 and statistical package for social sciences (SPSS) version 21 were used for data entry and analysis. The results are expressed as percentages and proportions. Results: In our study majority of the interns 66 (64.1%) had normal body mass index (BMI). The practice of non-exercise physical activity is more in female than male interns whereas the exercise physical activity is more in males comparing to female interns. Conclusions: Physical inactivity is an urgent public health priority, so long-term follow-up is needed to identify the factors promoting for the practice of physical activity among medical interns.